Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 4 - Section 4.2 - Solving Systems of Linear Equations by Substitution - Exercise Set: 12

Answer

x = 7 y = -4

Work Step by Step

x + 3y = -5 2x + 2y = 6 To the first equation minus 3y to both sides x + 3y - 3y = -5 - 3y x = -5 - 3y 2 ( -5 - 3y ) + 2y = 6 substitude x to the second equation - 10 - 6y + 2y = 6 simplify - 10 - 4y = 6 - 10 - 4y + 10 = 6 + 10 add 10 to both sides - 4y = 16 4y = - 16 multiply by -1 to both sides $\frac{4y}{4}$ = - $\frac{16}{4}$ divide by 4 to both sides y = - 4 substitude y for -4 to the first equation x + 3(-4) = -5 x - 12 = -5 x - 12 + 12 = -5 + 12 x = 7
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.